(untitled) (Revista Cocar, 2022)
O presente artigo analisa o discurso político de sujeitos governamentais que protagonizaram ações voltadas à Educação Básica no município de Belém, Estado do Pará, no período concernente aos anos de 1993 a 1996. Os denominados Cadernos Caminhos da Educação, publicados pela Secretaria de Educação Municipal (SEMEC), são tomados como corpus empírico da Análise de Discurso (AD) que se buscou implementar. Conclui-se que o conteúdo manifesto desses Cadernos teve seu sentido atrelado ao progresso técnico da modernidade capitalista, à ideologia do desenvolvimento sustentável e a certa visão messiânica e redentora da educação escolar como fator do desenvolvimento humano. Palavras-chave: Educação Ambiental; Ideologia; Desenvolvimento Sustentável Abstract This article analyzes the political discourse of governmental subjects who carried out actions aimed at Basic Education in the municipality of Belém, State of Pará, in the period from 1993 to 1996. The so-called Paths of education notebooks, published by the Department of Education Municipality (SEMEC), they are taken as an empirical corpus of the Discourse Analysis (AD) that we sought to implement. It is concluded that the manifest content of these notebooks had its meaning linked to the technical progress of capitalist modernity, to the ideology of sustainable development and to a certain messianic and redemptive vision of school education as a factor of human development. Key words: Discourse analysis; educational political discourse; Paths of education notebooks; Sustainable development.